Percutaneous transhepatic sclerotherapy for recurrent bleeding ileal varices diagnosed by capsule endoscopy and computed tomography during percutaneous transhepatic venography. Issue 4 (7th April 2013) - Hashimoto, Yoshimasa; Amano, Hajime; Fukumoto, Akira; Amano, Mio; Sagami, Shintaro; Yamao, Kentaro; Iiboshi, Tomohiro; Onogawa, Seiji; Hirano, Naomichi; Hanada, Keiji; Hino, Fumiaki
<x xml:space="preserve">Abstract</x> We report a case of acute uncontrolled gastrointestinal bleeding in a patient with liver cirrhosis. A 64‐year‐old man was admitted to our hospital for further investigation of blood in stools. Preliminary examination by computed tomography (CT) as well as upper and lower endoscopy could not detect the bleeding source. Exploratory laparotomy was considered difficult due to potential easy bleeding and adhesions caused by past abdominal surgery. The hemoglobin level was normalized by blood transfusion. Capsule endoscopy (CE) identified ileal varices. The top of these ileal varices was red, prompting their identification as the source of bleeding. Percutaneous transhepatic venography (PTV) confirmed the presence of many varices in the branch of the superior mesenteric vein, although the bleeding source could not be identified. CT during PTV identified varices protruding into the ileal lumen, which were managed subsequently by percutaneous transhepatic sclerotherapy (PTS). The procedure stopped the bleeding completely. CE proved less invasive and effective in detecting obscure gastrointestinal bleeding. CT during PTV followed by PTS is suitable for diagnosis and treatment of bleeding varices in patients with portal hypertension.